Development of Desirable Characteristics of Students For being School of morality through action research : a case study of ‎Phayakkaphumwittayakarn School - Srisettha, Surapong; Thee-asana, Siri; Ruangsuwan, Chayakan (Journal for Developing the Social and Community, 2020)
This research objectives were : 1) to study about the current situation and determine needs of desirable characteristics development of students in the extra large-size secondary school under MahaSarakham Office of Secondary Education Service Area 26 ; 2) to develop of desirable characteristics of students of Phayakkaphumwittayakarn School for being school of morality through action research and ; 3) to verify the result of the development of desirable characteristics of students in Phayakkaphumwittayakarn School for being school of morality. The research consisted 3 phases. The first phase was the study about the current situation and the expectation in the development of desirable characteristics of students for being school of morality, the second phase was the development of desirable characteristics of students for being school of morality through action research and the third phase was the verifying of the development result of desirable characteristics of students for being school of morality. The research instruments were the questionnaire, performance assessment, interview, observation and group meeting record form. The quantitative data analysis was enumerated to Mean and Standard Deviation, presented in the form of a composite table and Content Analysis was used for the quality data analysis. The results were as follows: (1) The study about the current situation and determine needs of desirable characteristics of students in the extra large-size secondary school under MahaSarakham Office of Secondary Education Service Area 26 on the discipline, learning attendance, commitment to work were in the low level and should be developed urgently. (2) The development result of desirable characteristics of students in Phayakkaphumwittayakarn School for being school of morality through Action Research was students had the highest level of behavior in all aspect. (3) To verify the result of development of desirable characteristics of students in Phayakkaphumwittayakarn School for being school of morality found that Phayakkaphumwittayakarn School is suitable for being a school of morality on discipline, pursuing learning and commitment to work.